Ambient intelligence : 14th European Conference, AmI 2018, Larnaca, Cyprus, November 12-14, 2018, Proceedings /: 14th European Conference, AmI 2018, Larnaca, Cyprus, November 12-14, 2018, Proceedings. (2018) - Unknown
No abstract available